2017
DOI: 10.1016/j.pedhc.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Telehealth and Care Coordination on the Number and Type of Clinical Visits for Children With Medical Complexity

Abstract: Introduction The purpose of this analysis was to evaluate the effects of an advanced practice nurse-delivered telehealth intervention on health care utilization by children with medical complexity (CMC). Because CMC account for a large share of health care utilization costs, finding effective ways to care for them is an important challenge requiring exploration. Method This was a secondary analysis of data from a randomized clinical trial with a control group and two intervention groups. The focus of the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…Those published focus on the use of videoconferencing alone and demonstrated that videoconferencing increases family satisfaction, and decreases travel, ED, office visits, and hospitalizations for CMC. 13,14…”
Section: Introductionmentioning
confidence: 99%
“…Those published focus on the use of videoconferencing alone and demonstrated that videoconferencing increases family satisfaction, and decreases travel, ED, office visits, and hospitalizations for CMC. 13,14…”
Section: Introductionmentioning
confidence: 99%
“…15 Providing care coordination via telehealth also was associated with a decrease in unplanned visits. 16 In a further study, interviews with health care providers involved in care coordination demonstrated that success with care coordination generally involved proactive rather than reactive coordination of services, providing services such as pre-visit assessments, and using family questionnaires regarding priorities and goals, as well as written care plans. 27 Despite a growing evidence base on successes with care coordination, some challenges remain.…”
Section: Discussionmentioning
confidence: 98%
“…14 Several organizations recently have reported success with adopting new methods of care coordination. [15][16][17] The Patient Protection and Affordable Care Act (ACA) may have provided further impetus to implement health care coordination initiatives. 18 Increasing adoption of care coordination services for CSHCN could have reduced disparities in access to care coordination, as compared to disparities noted in studies using older data.…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed that online asthma management is both clinically effective and cost-effective and can partly replace outpatient visits [ 9 ]. Study by McKissick et al showed that telehealth intervention delivered by advanced practice registered nurse to children with medical complexity led to reduction in number of unplanned health care visits (due to acute deterioration in child’s condition) and increase in planned visit (for regular health maintenance) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%